Isolation and characterization of intact cardiomyocytes from frozen and fresh human myocardium and mouse hearts - Liu, Honghai (Methods Mol Biol, 2021)
Procurement and characterization of intact human cells is essential for studies in regenerative medicine and translational medical research. The selection of the currently available approaches to isolate intact cells depends on the age of the hearts. To isolate cardiomyocytes from the fetal or neonatal myocardium, the myocardium can be minced into small tissue blocks followed by enzyme incubation. However, the fetal and neonatal cardiomyocytes are very soft and the morphology changes from long-rod or spindle shape to spheres after isolation. Because the dense packing of the cardiomyocytes and the strong cell-cell connection in adult myocardium, it is difficult to isolate the cardiomyocytes from adult myocardium only by enzyme incubation. Perfusion method is necessary to deliver the enzyme solution to the deep layers of the myocardium. However, intact hearts, which is very rare, are required for perfusion method. Therefore, lacking methods to efficiently isolate cardiomyocytes from myocardium of various ages builds a barrier between basic research and clinical studies. Here, we describe a method for the isolation of intact cardiomyocytes from fresh or frozen human myocardium or fresh mouse hearts and the quantification of multinucleation, cardiomyocyte size, cell cycle activity, and total cardiomyocyte count per heart. We generalize this fixation-digestion method by isolating cells from a variety of mouse organs, including the liver, lung, and thymus.